2016
DOI: 10.1111/vop.12386
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical diclofenac, topical flurbiprofen, and humidity on corneal sensitivity in normal dogs

Abstract: Neither diclofenac nor flurbiprofen had an effect on corneal sensitivity after multiple-drops or twice-daily dosing for 30 days. Ambient humidity may have an effect on corneal sensitivity measurements, with a longer filament length eliciting a blink response at lower humidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
2
18
1
Order By: Relevance
“…It is possible that the anti-inflammatory action of ketorolac may reduce the irritant effect of benzalkonium chloride on corneal nociceptor fibers. The results of flurbiprofen and diclofenac identified in the current study are somewhat different than the results obtained in a recent study (Dorbandt et al, 2017), and this may be explained, in part, by variations in study design as well as differences in ambient humidity between the two studies. The current study evaluated corneal sensitivity with decreasing increments of 0.25 cm, and this may have allowed the investigators to assess for smaller changes in corneal sensitivity.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…It is possible that the anti-inflammatory action of ketorolac may reduce the irritant effect of benzalkonium chloride on corneal nociceptor fibers. The results of flurbiprofen and diclofenac identified in the current study are somewhat different than the results obtained in a recent study (Dorbandt et al, 2017), and this may be explained, in part, by variations in study design as well as differences in ambient humidity between the two studies. The current study evaluated corneal sensitivity with decreasing increments of 0.25 cm, and this may have allowed the investigators to assess for smaller changes in corneal sensitivity.…”
Section: Introductioncontrasting
confidence: 99%
“…One of the most important differences between the two studies is the ambient humidity. In the current study, ambient humidity values during data collection were 71% to 77%, and it has been shown that humidity may have profound effects on corneal esthesiometry measurements (Dorbandt et al, 2017). In the recent comparable study, ambient humidity ranged from 19% to 44%, which may explain the higher sensitivity values, as the same study found that a lower humidity http://www.openveterinaryjournal.com R. Cantarella et al Open Veterinary Journal, (2017), Vol.…”
Section: Introductionmentioning
confidence: 50%
See 3 more Smart Citations